Green synthesis of silver nanoparticles derived from algae and their larvicidal properties to control Aedes aegypti - Matheus Alves Siqueira de Assunção; Douglas Dourado; Daiane Rodrigues dos Santos; Gabriel Bezerra Faierstein; Mara Elga Medeiros Braga; Severino Alves Junior; Rosângela Maria Rodrigues Barbosa; Herminio José Cipriano de Sousa; Fábio Rocha Formiga (Beilstein Journal of Nanotechnology)
Mosquito vectors such as Aedes spp. are responsible for the transmission of arboviruses that have a major impact on public health. Therefore, it is necessary to search for ways to control these insects, avoiding the use of conventional chemical insecticides that are proven to be toxic to nature. In the last years, there has been growing evidence for the potential of silver nanoparticles (AgNPs) to be ecologically benign alternatives to the commercially available chemical insecticides against vector-borne diseases. Natural seaweed extracts contain metabolites such as polyphenols, terpenoids, and alkaloids. These compounds act as reducing agents and stabilizers to synthesize biogenic AgNPs. The green synthesis of AgNPs has advantages over other methods, such as low cost and sustainable biosynthesis. In the perspective of using AgNPs in the development of novel insecticides for vector control, this review deals with the eco-friendly synthesis of AgNPs through seaweed extracts as reducing and stabilizing agents. In addition, assessment of toxicity of these nanomaterials in non-target species is discussed.